Ultrasmall Pd‐Cu‐Pt Trimetallic Twin Icosahedrons Boost the Electrocatalytic Performance of Glycerol Oxidation at the Operating Temperature of Fuel Cells. (23rd January 2020) - Yang, Fang; Ye, JinYu; Yuan, Qiang; Yang, Xiaotong; Xie, Zixuan; Zhao, Fengling; Zhou, Zhiyou; Gu, Lin; Wang, Xun
Abstract: Recently, in order to improve the energy conversion efficiency of direct polyol fuel cells, the engineering of effective Pd‐ and/or Pt‐based electrocatalysts to rupture CC bonds has received increasing attention. Here, an example is shown to synthesize highly uniform sub‐10 nm Pd‐Cu‐Pt twin icosahedrons by controlling the nucleation phase. Because of the synergies of the electronic effect, synergistic effect, geometric effect, and abundant surface active sites originating from the formation of near surface alloy and special icosahedral shape, the Pd‐Cu‐Pt twin icosahedrons exhibit excellent electrocatalytic performance in glycerol electrocatalysis at the operating temperature of direct alcohol fuel cells (70 °C) in KOH electrolyte. The Pd50.2 Cu38.4 Pt11.4 icosahedrons show mass activities of 9.7 A mg −1 Pd+Pt and 13.7 A mg −1 Pd . Furthermore, the Pd50.2 Cu38.4 Pt11.4 icosahedrons demonstrate long‐term durability in current–time test for 36 000 s and high in situ anti‐CO poisoning performance. In addition, the introduction of CO can enhance electro‐oxidation endurance on Pd50.2 Cu38.4 Pt11.4 icosahedrons, and the peak mass activity can reach to 14.4 A mg −1 Pd+Pt . The in situ Fourier transform infrared spectroscopy spectra indicate that the Pd50.2 Cu38.4 Pt11.4 icosahedrons possess a high capacity to break CC bonds and may efficiently convert glycerol into CO2, thus improving the utilization efficiency of energy‐containing molecule glycerol. Abstract : Ultrasmall Pd‐Cu‐Pt trimetallic twin icosahedrons have been achieved as effective electrocatalysts toward glycerol oxidation at the operating temperature of fuel cells (70 °C). The Pd50.2 Cu38.4 Pt11.4 icosahedrons exhibit a high capacity to break CC bonds, long‐term durability in current–time test for 36 000s, and high in situ anti‐CO poisoning performance.